Digital Transformation of Islamic Financial Institutions: Opportunities and Challenges in Reaching Unbanked Communities - Hidayat, Rahmat; Syafirah , Aulia; Yuniar, Ashey (Program Studi Perbankan Syariah Fakultas Ekonomi dan Bisnis Islam UIN Datokarama Palu, 2025)
Digital transformation has become a major driver in financial services innovation, including in Islamic financial institutions. Amid the increasing need for financial inclusion, digitalization presents a great opportunity for Islamic financial institutions to expand the reach of their services, especially to unbunked segments of society, namely individuals or groups that do not have formal financial services. This study aims to explore the dynamics of digital transformation in Islamic financial institutions, by highlighting the potential and challenges faced in accessing and serving the unbunked community. The type of qualitative research is used using a literature review approach and descriptive analysis of various literature that supports the research. The results of the analysis show that digitalization through Islamic mobile banking, Islamic fintech platforms, and the use of big data is able to reduce geographical barriers, transaction costs, and increase budget efficiency. However, the main challenges faced by the community itself range from literacy, understanding, uneven technological infrastructure, and lack of public trust. With the right strategy, digital transformation not only strengthens the competitiveness of Islamic financial institutions, but also becomes an effective solution in reaching and deceiving unbunked communities.